Insights into the Molecular Events That Regulate Heat-Induced Chilling Tolerance in Citrus Fruits - Lafuente, María T.; Establés-Ortíz, Beatriz; González-Candelas, Luis (Frontiers in Plant Science, 2017)
Low non-freezing temperature may cause chilling injury (CI), which is responsible for external quality deterioration in many chilling-sensitive horticultural crops. Exposure of chilling-sensitive citrus cultivars to non-lethal high-temperature conditioning may increase their chilling tolerance. Very little information is available about the molecular events involved in such tolerance. In this work, the molecular events associated with the low temperature tolerance induced by heating Fortune mandarin, which is very sensitive to chilling, for 3 days at 37 ºC prior to cold storage is presented. A transcriptomic analysis reveals that heat-conditioning has an important impact favoring the repression of genes in cold-stored fruit, and that long-term heat-induced chilling tolerance is an active process that requires activation of transcription factors involved in transcription initiation and of the WRKY family. The analysis also shows that chilling favors degradation processes, which affect lipids and proteins, and that the protective effect of the heat-conditioning treatment is more likely to be related to the repression of the genes involved in lipid degradation than to the modification of fatty acids unsaturation, which affects membrane permeability. Another major factor associated with the beneficial effect of the heat treatment on reducing CI is the regulation of stress-related proteins. Many of the genes that encoded such proteins are involved in secondary metabolism and in oxidative stress-related processes.